"Determined to Suppress Everything Like Free Speech": Lincoln's Private Letters Reveal Aggressive Use of Newspaper Censorship. Issue 2 (2nd April 2020) - Banning, Stephen
ABSTRACT: This research contrasts two times President Abraham Lincoln suppressed the American Civil War opposition press. Original letters from Lincoln and those involved in the suppressions shed light on Lincoln's involvement. The findings suggest that Lincoln himself allowed press suppression to continue even when it would influence a local election. Contrary to some beliefs, it appears Lincoln did not soften his approach to press suppression during the latter part of the Civil War. The question "What did the President know and when did he know it?" has never been properly answered. This research examines the actual letters among suppression principals including President Lincoln to acquire a feeling for what was specifically being said, and not being said, at the time, specifically, Lincoln's attitude toward free speech. At the time, some suggested Lincoln allowed speech to be suppressed, while others have claimed he did not. Many books have documented Lincoln's public words on the subject, but Lincoln's private letters are even more revealing in the case of press suppression.